Superior interface properties and unusual deformation mechanisms of high-entropy alloys through explosive welding - Yaping Zhou; Ze Hua; Lei Li; Yinxin Tan; Jiaohui Yan; Zhihui Lin; Wen Yang; Ke Jin; Ruiwen Shao; Tiansheng Liu (Journal of Materials Research and Technology)
Refractory high-entropy alloys (RHEAs) have been extensively studied due to their remarkable properties. However, their complex preparation processes and high production costs limit their engineering applications. In this study, we successfully fabricated RHEAs TiVTaNb and titanium (Ti) composite plates through explosive welding technology, utilizing a self-optimized groove device. A systematic investigation was conducted to examine the micro-mechanical properties and the microstructural evolution at the weld interfaces. The results revealed a 12% increase in hardness at the weld interface. Microcolumns near the interface exhibited minimal dislocation slip, and their compressive strength was found to be approximately twice that of regions further from the interface. Electron backscattered diffraction (EBSD) and transmission electron microscopy (TEM) analyses showed a significant increase in dislocation density and the presence of twinning near the weld interface. The accumulation of dislocations in this region is considered a critical factor influencing both the microstructural evolution and the mechanical properties of the weld interface. These findings offer valuable insights and provide a robust foundation for the future engineering applications of RHEA-based composite materials.